PSYCHOLOGICAL PREDICTOR VARIABLES OF EVOLUTION IN A THERAPEUTIC COMMUNITY - Santos Diez, Patxi; García Merita, Mª Luisa; Barreto Martín, María Pilar (Anales de Psicología / Annals of Psychology, 2001)
Objective: To study the possible predictive capacity of different psychological variables on the evolution from the subjects as of the sixth month of processing in a Therapeutic Community - Unidad de Deshabituación Residencial (U.D.R.). Method: The sample is composed by 47 subjects (6 women and 41 men) heroin addicts that made processing in the Therapeutic Community "Balsa Blanca". The psychological evaluation was made with following questionnaires: 16-PF, BDI and STAI. It was carried out a regression of Cox and a discriminante analysis. Results: the regression of Cox selected a assembly of four predicting variables, of such form which those subjects that at the beginning of processing obtained discharges scores in sensitivity last (trusted itself, realistic),analytical-critic (liberal, experimental), self-sufficient and little controlled socialization had more probabilities of leaving after six months of processing. Discriminate analysis selected a assembly of two psychological variables that present/display great predictive value when classifying correctly the 93,68% of the subjects that leave: I (sensitivity lasts) and QIII- (little controlled socialization). Conclusions: The knowledge of these predicting variables of abandonment in U.D.R. can serve to improve the design and the planning of the processing helping to prevent the injurious effects with the same ones.